Pelatihan Inovasi Teknologi Pengolahan Virgin Coconut Oil (VCO) Berbasis Potensi Lokal dan Legalitas Usaha - Chatryen M Dju Bire; Yuri Sandra Fa’ah; Vinsensius Manet Ati; Juliana Susantje Ndolu; Bernaldino Devistro; Treza Eanda Kapitan; Arista Apriani Bifel; Dortius K. Lihu; Jenifer Viola Agustina Sengge; Grace Djara Rohi (Penerbit Goodwood, 2026)
Purpose: The community service activity was carried out to provide a comprehensive understanding and improve the skills of participants in the aspects of production and processing technology of Virgin Coconut Oil (VCO), business management, and marketing. Methodology/approach: The program was implemented in three stages: preparation, implementation, and evaluation. It involved 25 members from the Meusin Village Disaster Preparedness Group and 20 members from the Saving and Loan Cooperative. The team consisted of four lecturers and 14 students, and the training covered VCO production, business management, and marketing. Results/findings: The participants actively engaged in all stages, achieving 100% attendance. They learned VCO production, from coconut selection to packaging, and increased their skills in labeling, marketing via social media, and basic bookkeeping. Within seven days, the groups produced 53 bottles of 100 mL VCO. Additionally, they obtained Business Identification Numbers (NIBs). Conclusions: The activity successfully enhanced participants' skills and knowledge in production, business management, and digital marketing. Limitations: The limitation of this activity is that product quality and shelf-life testing have not been carried out. Contributions: This activity was able to achieve the results that had been previously targeted.